2021
DOI: 10.3390/en14030721
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Melting Process in Phase Change Material Windows Determined Based on Direct Light Transmission

Abstract: Detailed analyses of melting processes in phase change material (PCM) glazing units, changes of direct transmittance as well as investigation of refraction index were provided based on laboratory measurements. The main goal of the study was to determine the direct light transmittance versus time under constant solar radiation intensity and stable temperature of the surrounding air. The experiment was conducted on a triple glazed unit with one cavity filled with a paraffin RT21HC as a PCM. The unit was installe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…One of the specific examples of PCM containers is PCM-glazing [32,33], which is characterized by transparent or semi-transparent (translucent) properties. The optical characteristics [34,35], as well as the dynamics of the melting process [36,37], have been investigated in the past. Studies have confirmed that the PCM transmittance changes significantly due to the change of phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the specific examples of PCM containers is PCM-glazing [32,33], which is characterized by transparent or semi-transparent (translucent) properties. The optical characteristics [34,35], as well as the dynamics of the melting process [36,37], have been investigated in the past. Studies have confirmed that the PCM transmittance changes significantly due to the change of phase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thermal processes during the change of phase have been defined in a simplified way when the PCM layer is treated as a body of uniform. Heim et al [36] made an experiment for a triple glazed PCM window irradiated by an artificial sun. It was confirmed that the transmittance of PCM does not change linearly and the melting process in a PCM cavity is more complex, with regions of solid, mushy and melted layers.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, et al [9] studied the impact of the refractive index and extinction coefficients for a glazed roof filled with PCM in liquid and solid states. Heim, et al [10] determined the direct light transmittance of a triple glazed unit with one cavity filled with PCM under constant solar radiation intensity and stable air temperature. They found that the interreflections inside the PCM glazing during the phase change cause nonuniformity in the light transmission.…”
Section: Introductionmentioning
confidence: 99%